Importance Of Interpersonal Relationship Reflected In Tom Hooper's The King's Speech Movie (2010): A Humanistic Psychological Approach - SETIADI, NUROHMAN (2012)
This study is aimed to show the importance of interpersonal relationship in The King's Speech movie by using Humanistic Psychological Approach. The object of the study are to analyze the structural of the movie and to analyze the movie based on the humanistic psychological perspective. This study is conducted by using qualitative method. The researcher uses two data sources which namely primary data and secondary data sources. The primary data source is The King's Speech movie, the secondary data source are the books about Psychological, some books about Humanistic, and another virtual references. Next, the other sources which are related to this analysis.The writer collects the data from both primary and secondary data sources by note taking and image capturing and also using library research. The technique of data analysis is descriptive technique. The result of the study shows that first, based on the structural analysis of each elements, it shows that the character and characterization, casting, plot, setting, point of view, theme, cinematography, mise_en_scene, sound, and editing are related to each other. Secondly, from humanistic psychological perspective, one of characters' self actualization is interpersonal relationship that is influenced by three aspects; communication, self disclosure, and acceptance. Tom Hooper reflects phenomenon of humanistic psychology that is someone who has motivation to solve his problem by interpersonal relationship with other people.